СПОСОБЫ УПРАВЛЕНИЯ ПРОСТРАНСТВЕННЫМ ПОЛОЖЕНИЕМ НАНОСПУТНИКА - Явіся, Валерій Сергійович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
A method of controlling the spatial location of nano-satellites The analysis of methods of orientation and stabilization of the spatial position of the ultra-small spacecraft. Traditional methods of orientation and stabilization are measured in terms of their feasibility, taking into account the restrictions on weight and overall performance, operational constraints associated with the consumption of energy here, as well as the possibility of changing orbit.